Metastatic Melanoma to the Urinary Bladder of Ocular Origin Accompanied with Primary Cutaneous Melanoma: Diagnostic Challenge—A Report of a Case - Constantine Theocharides; Kyriakos Chatzopoulos; Dimitrios Papanikolaou; Vasileios Siokas; Ioannis Amplianitis; Athanasios Papanikolaou (Case Reports in Pathology)
Metastases of melanoma to the urinary bladder are infrequent. Even rarer are metastases to the urinary bladder from uveal melanoma, with only 3 cases published in the literature so far. Herein we present a case of a 77-year-old male patient who presented with metastatic melanoma to the urinary bladder. The patient’s history included the diagnoses of uveal melanoma treated with radiation 25 years ago, as well as that of cutaneous melanoma diagnosed 7 years ago. The molecular study of the urinary bladder tumor specimen identified mutation of the GNAQ gene, which has been suggested to be an early molecular event in the pathogenetic course of over 80% of uveal melanomas. Therefore, the diagnosis of uveal melanoma metastatic to the urinary bladder was made.